2006
DOI: 10.1159/000094586
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, Abdominal Obesity and Alzheimer Disease

Abstract: Background/Aims: Obesity has a strong association with vascular and metabolic diseases, which have been linked with Alzheimer disease (AD). While recent studies have reported an association between mid-life obesity and dementia, the role of later-life obesity is less clear. This study investigated the relation between AD, obesity and abdominal obesity at later-life in a case-control study. Methods: Participants were 50 consecutive patients with probable AD from memory disorders clinics in Launceston, Australia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
72
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(76 citation statements)
references
References 35 publications
2
72
1
1
Order By: Relevance
“…Recently, particular attention has focused on the presence of a longitudinal link between middle-age adiposity [32,33] and later-life obesity [34,35] and the decline in cognitive function. Thus, obesity seems responsible for further health implications beside cardiovascular disorders (CVD), and the presence of a vascular burden is recently recognised as a possible common cofactor in the development of dementia [33].…”
Section: Sd: Standard Deviation Hdl-c: High Density Lipoprotein Cholmentioning
confidence: 99%
“…Recently, particular attention has focused on the presence of a longitudinal link between middle-age adiposity [32,33] and later-life obesity [34,35] and the decline in cognitive function. Thus, obesity seems responsible for further health implications beside cardiovascular disorders (CVD), and the presence of a vascular burden is recently recognised as a possible common cofactor in the development of dementia [33].…”
Section: Sd: Standard Deviation Hdl-c: High Density Lipoprotein Cholmentioning
confidence: 99%
“…Central obesity has a strong correlation with cardiovascular disease [1] and has been linked to Alzheimer's disease and type 2 diabetes [2], as well as other metabolic and vascular diseases [3]. Enzyme cholinesterase is present in all mammals and two classes have been identified as acetylcholinesterase (AChE, EC 3.1.1.7) and butyrylcholinesterase (non-specific, pseudocholinesterase, BChE; EC 3.1.1.8) in serum.…”
Section: Introductionmentioning
confidence: 99%
“…While the link between obesity and insulin resistance, metabolic syndrome, and T2DM is widely appreciated, emerging data indicate that mid-life obesity also increases risk for late-life dementia and AD [9,10,12,20,26,27,31]. Abdominal obesity, indexed as the waist-hip ratio, has also been associated with an increased risk for AD [26].…”
Section: Introductionmentioning
confidence: 99%
“…Abdominal obesity, indexed as the waist-hip ratio, has also been associated with an increased risk for AD [26]. In addition, recent studies demonstrated that plasma Aβ levels were directly related to BMI in a small group of young, non-demented individuals [1] and adipocyte APP expression levels [14].…”
Section: Introductionmentioning
confidence: 99%